ANALISIS EFEKTIVITAS CORPORATE SOCIAL RESPONSIBILITY DALAM PROGRAM KEMITRAAN BADAN USAHA MILIK NEGARA (Studi Kasus pada Perkembangan UMKM Mitra Binaan PT. Perkebunan Nusantara VII Unit Usaha Rejosari) - Maulana Agung Pratama (Yogyakarta State University, 2013)
One of theCorporate Social Responsibility program in BUMN is the Partnership Program. Partnership Program is a program designed specifically for Micro, Small and medium enterprise development to be sustainable, self sufficient and have competitive power using funds benefit from BUMN profits. The purpose of this reasearch are to describe effectiveness of BUMN partnership program that have been implemented by PT. Perkebunan Nusantara VII. The type of this research is descriptive by using qualitatif approaching. Analyse effectiveness of Partnership Program which contain of two indicators: first accuracy of implementation BUMN Partnership Program and the second is micro, small and medium enterprise growth, with nine informan, they are four people from PKBL staff of PT. Perkebunan Nusantara VII, Unit Usaha Rejosari branch and five people from micro, small and medium enterprise Partnership Program. According to the result of research done by using interview, observation and documentation so the researcher can conclude that Effectivenees of Partnership Program in the micro, small and medium enterprise growth has runs effectively and accordance with the objectives of the Partnership Program, all can be proved from the conclusions from each indicator of the effectiveness. The recommendation for Partnership Program PT. Perkebunan Nusantara VII is to evaluate the results of the Partnership training program that has been given for development of micro, small and medium enterprise Pertnership Program, micro, small and medium enterprise also need to be trained formastery of information technology not only management training, and micro, small and medium enterprise Partnership Program must provide monthly financial reports to PT. Perkebunan Nusantara VII.Key words: Effectivenees, Partnership Program, micro small and medium enterprise